Eletrodos voltamétricos à base de nanotubos de carbono verticalmente alinhados aplicados na determinação de estatinas em formulações farmacêuticas e fluidos biológicos - Silva, Tiago Almeida (2015)
In this work the application of electrodes based on a composite of Vertically Aligned Carbon Nanotubes and Graphene Oxide (VACNT-GO) as electrochemical sensor for the determination of pharmaceuticals from the statin class was explored. The VACNT-GO composite was synthesized by the Microwave Chemical Vapour Deposition (MWCVD) method, followed by oxygen plasma treatment. Using high-resolution scanning electron microscopy, Raman spectroscopy and X-Ray photoelectron spectroscopy, it was possible to verify the exposition of graphene sheets functionalized with oxygenated groups (graphene oxide) in the VACNT tips after the oxygen plasma treatment. The oxygen content increased from 4.9% for the VACNT sample to 21.4% in the VACNT-GO sample case. Furthermore, the C:O ratio was equal to approximately 1.5 for the VACNT-GO sample, in accordance with the expected range for graphene oxide. Moreover, by measurements of the contact angle with distillated water, it was noted a drastic change of the sample surface wettability, changing from superhydrophobic for VACNT (contact angle = 157o) to superhydrophilic for VACNT-GO (contact angle ≈ 0o), enhancing the electrochemical application of the material in aqueous systems. From cyclic voltammetry assays conducted for the potassium hexacyanoferrate (III) probe, it was diagnosticated an electroactive area equivalent to approximately 80% of the geometric area and a high heterogeneous electron transfer rate constant (3.4 × −2 −110 cm s ) for the VACNT-GO electrode, demonstrating the good electrochemical performance of the proposed electrodic material. Next, voltammetric methods for determination of the statins atorvastatin calcium (ATOR) and rosuvastatin calcium (ROS) were developed. Using Differential Pulse Adsorptive Anodic Stripping Voltammetry (DPAdASV) under optimized conditions, the constructed analytical curve for ATOR was linear in the range −8 −6 −1 −9from 9.0 × 10 to 3.8 × 10 mol L , with a limit of detection of 9.4 × 10 mol −1L . In the ROS drug case, the Square-Wave Adsorptive Anodic Stripping Voltammetry (SWAdASV) technique showed the better analytical performance, and also under optimized conditions, the analytical curve was linear in the ROS −7 −5 −1concentration range from 4.8 × 10 to 4.7 × 10 mol L , with a limit of −8 −1detection of 6.0 × 10 mol L . Both the voltammetric procedures were successfully applied in the ATOR and ROS determination in pharmaceutical formulations and synthetic biological samples (urine and human serum).